2019
DOI: 10.1159/000504911
|View full text |Cite
|
Sign up to set email alerts
|

Race and Ethnicity Gaps in Global Hidradenitis Suppurativa Clinical Trials

Abstract: Background: Hidradenitis suppurativa (HS) is an often-debilitating disease characterized by chronic and recurrent painful nodules, abscesses, and sinus tracts affecting the intertriginous areas. Despite evidence in the literature of varying prevalence of HS among different racial and ethnic groups, no studies have evaluated the overall generalizability of clinical trial results considering the increased prevalence of HS among African American populations. Additionally, there is a paucity of data exploring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…Much remains to be learned about the influence of race on the pathogenesis of HS. Unfortunately, the vast majority of HS studies have failed to report participants’ race or ethnicity 60 . Adequate representation of diverse patients across all demographic groups including race and ethnicity is critical to enhancing our understanding of disease pathogenesis and ensuring that treatments can meet the needs of all subgroups affected by this debilitating disease.…”
Section: Racial Background and Hsmentioning
confidence: 99%
“…Much remains to be learned about the influence of race on the pathogenesis of HS. Unfortunately, the vast majority of HS studies have failed to report participants’ race or ethnicity 60 . Adequate representation of diverse patients across all demographic groups including race and ethnicity is critical to enhancing our understanding of disease pathogenesis and ensuring that treatments can meet the needs of all subgroups affected by this debilitating disease.…”
Section: Racial Background and Hsmentioning
confidence: 99%
“…The remaining 144 (14.6%) participants were recorded as “other/unspecified” (36 self-identified, 108 lacked race reporting). None of the trials included a subanalysis of treatment efficacy based on race or ethnicity 51 .…”
Section: Hs Unmet Needsmentioning
confidence: 99%
“…One study was conducted solely in Caucasian and Romany individuals 52 , while another study consisted of 80–85% Caucasians 38 . Furthermore, none of the trials reported the percentage of patients who were Hispanic or stratified results by race 51 . The other systemic biologic agent trials for HS (e.g.…”
Section: Hs Unmet Needsmentioning
confidence: 99%
“…[49] This is especially important in dermatology, as dermatological care has traditionally focused on lighter-skinned and higher SES populations. [1], [2], [50] Figures Figure 1 Percent of racial/ethnic group with respect to their frequency of sunscreen use.…”
Section: Resultsmentioning
confidence: 99%